Women in Botany and the Canadian Federal Department of Agriculture, 1887-1919 - Loydlangston, Amber (Scientia Canadensis, 2006)
AbstractThis article explores the nature of women's involvement in the science of botany in the federal Department of Agriculture from 1887 to 1919. It argues that the professionalization and bureaucratization of science in the department created distinct opportunities for women but also confined them to specific jobs deemed appropriate for their sex. Because the botany that was first undertaken in the department emerged from the natural history tradition, women first contributed as unpaid "amateur" observers, collectors, and correspondents. As science professionalized and bureaucratized in the late nineteenth and early twentieth centuries, however, the contributions of unpaid "amateurs" were no longer desired or needed. At this juncture, women were employed as paid assistants and members of the support staff. As civil servants, women entered an organization that was undergoing a process of professionalization and bureaucratization. As a result, women were subjected to hierarchical and territorial segregation, undertaking 'women's work' in botany. They performed tasks which were undervalued, underpaid, and offered little or no opportunity for advancement, and were, therefore, rejected by men. Satisfying the demands generated by the professionalization and bureaucratization of science as well as of the federal civil service, women were a pivotal part of the botanical workforce of the Canadian federal Department of Agriculture from 1887 to 1919.